2020
DOI: 10.21203/rs.3.rs-24133/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Association between neutrophil-to-lymphocyte ratio, platelet-to-lymphocyte ratio, and diabetic retinopathy among diabetic patients without a related family history

Abstract: Abstract Background: Diabetic retinopathy (DR) is a specific neurovascular complication of diabetes mellitus (DM). Clinically, family history is a widely recognized risk factor for DR,assisting diagnosis and risk strata. However, among a great amount of DR patients without hereditary history like hypertension and diabetes, direct and simple risk factors to assist clinical decisions are still required. Herein, we intend to investigate the associated risk factors for thes… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 34 publications
(38 reference statements)
1
6
0
Order By: Relevance
“…NLR was also considered a prognostic and predictive factor for DM and its complications [21,22]. Wang et al found that NLR was related to DR in patients with diabetes who had no associated family history in China [23]. Nevertheless, further research is required to determine whether this is the same in different regions, populations, and types of diabetes.…”
Section: Introductionmentioning
confidence: 99%
“…NLR was also considered a prognostic and predictive factor for DM and its complications [21,22]. Wang et al found that NLR was related to DR in patients with diabetes who had no associated family history in China [23]. Nevertheless, further research is required to determine whether this is the same in different regions, populations, and types of diabetes.…”
Section: Introductionmentioning
confidence: 99%
“…As a simple and economical experimental index, the PLR has been confirmed to be closely related to T2DM and its chronic complications, cardiovascular disease, peripheral arterial disease, and tumors 7‐17 . We found that the PLR was significantly elevated in patients with DFU and it was identified as an independent risk factor for DFU.…”
Section: Discussionmentioning
confidence: 63%
“…As a simple and economical experimental index, the PLR has been confirmed to be closely related to T2DM and its chronic complications, cardiovascular disease, peripheral arterial disease, and tumors. [7][8][9][10][11][12][13][14][15][16][17] We found that the PLR was significantly elevated in patients with DFU and it was identified as an independent risk factor for DFU. The results of the ROC curve further showed that the PLR could be used as a simple clinical indicator for the clinical diagnosis of DFU, which was consistent with the findings of a previous study.…”
Section: Discussionmentioning
confidence: 99%
“…Platelet to lymphocyte ratio (PLR), monocyte to lymphocyte ratio (MLR), and neutrophil to lymphocyte ratio (NLR) are potential inflammatory markers for diabetes and its complications (10)(11)(12). The associations between PLR, NLR, and MLR with DR progression have been described in the literature (13)(14)(15); however, the relationship between peripheral blood inflammatory markers and severe DR with DME remains to be clarified.…”
Section: Original Articlementioning
confidence: 99%